PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE MIND MAPPING UNTUK MENINGKATKAN HASIL BELAJAR PKn SISWA KELAS V SD NEGERI 59 SEBANGAR KECAMATAN MANDAU - Nur, Muhammad; Noviana, Eddy; Syahrilfuddin, Syahrilfuddin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research is motivated by the low learning outcomes Civics class V students of SD Negeri 59 Sebangar District of Saber, with an average grade 57.92. While the value of minimum completeness criteria (KKM) Civics is 70, among the students who totaled 24 people only 7 people who reach KKM. This research is a classroom action research (PTK) by applying cooperative learning model Mind Mapping. This thesis presents the results of studying the data obtained from the average results of study before action 57.92 increased to 64.79 in Cycle I. In the second cycle increased to 76.7. The activities of teachers in the first cycle of the first meeting of the percentage gain of 54.2% to the category, please, at the meeting of the two has increased roughly 75% of both categories. Furthermore, the first meeting of the second cycle activities of teachers also mengelami 79.2% increase in the percentage of both categories, and the second meeting of the second cycle increased by a percentage of 87.5% is very good category. Activity of students in the first cycle of the first meeting of the percentage of 58.3% enough category, at a second meeting has increased by 70.8% percentage of both categories, the first meeting with a percentage of 79.2% meniingkat both categories. At the second meeting of two cycles has increased with the percentage of 83.3% is very good category. Research in class V SD Negeri 59 Sebangar District of Saber Two proves that the implementation of cooperative learning model Mind Mapping can improve learning outcomes Elementary School fifth grade students Mandau sub 59 SebangarKey words: Model Cooperative Learning Mind Mapping,Learning Outcomes PKn